A Unified Model for the Adoption of Electronic Word of Mouth on Social Network Sites: Facebook as the Exemplar. Issue 2 (3rd April 2018) - Aghakhani, Navid; Karimi, Jahangir; Salehan, Mohammad
ABSTRACT: Electronic word of mouth (eWOM) has gained increased attention from both practitioners and academia. Its importance lies in its simplicity and yet its profound impact on customers' attitudes toward specific brands or goods, and thus affecting customers' loyalty and purchase behaviors. Although social network services (SNSs) have emerged as a new platform for eWOM communication, less attention has been paid in the literature to eWOM adoption on SNSs. Using the elaboration likelihood model (ELM) and the affect-as-information theory, this study identifies factors that affect eWOM adoption on Facebook. We identify product-related information in a review, source credibility, peer image building, and tie strength as theoretically important variables in our study, and we examine their effect on cognitive and affective attitudes. We find that eWOM types (explicit vs. implicit) moderate the effects of cognitive and affective attitude on eWOM adoption. We further find that the effect of cognitive attitude on eWOM adoption is higher when the eWOM is explicit, while the effect of affective attitude is higher when the eWOM is implicit. For information systems (IS) researchers, this study advances the eWOM adoption literature by highlighting the role of eWOM types in the eWOM adoption process and integrating the ELM and affect-as-information theories to explore the antecedents of eWOM adoption. For IS practice, this study also provides new insights for online retailers and social media marketers about the antecedents of eWOM adoption.